Quantitative Assessment of Vegetation Dynamics through Species Composition and Diversity Indices in Restoring Nandini Limestone Mines, Chhattisgarh - Maitry, Abhishek; Patil, Gunjan; Dubey, Preety (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted in the year 2023–24 for a duration of one year at Nandini Limestone Mines, District- Durg, Chhattisgarh, India with the objective to gather information about the floral diversity and to enable the presence or likely presence of components of flora before planning, conservation management, and development decisions for the specific area of land as mining activities have altered the land use patterns, leading to significant soil degradation and creating challenging conditions for plant growth. However, some plant species adapt well to these conditions and support ecological restoration. Studying such species is crucial for biodiversity conservation and effective land management in degraded areas. The baseline biodiversity survey with random quadrate sampling method was adopted in 25 different quadrats for vegetation analysis which resulted in the identification of a total of 136 species of terrestrial flora including 48 species of trees, 51 species of herbs and shrubs, 7 species of climbers, and 30 species of grasses. The Shannon-wiener index for tree species was 3.583, other diversity indices namely; Simpson’s index, Simpson’s index of diversity, Simpson’s reciprocal index, Evenness, and Margalef richness index were calculated at 0.034, 0.966, 29.412, 0.926 and 7.2845 respectively. The highest Family Importance Value Index (FIVI) was observed as 54.82 for the Fabaceae family whereas the highest Importance Value Index (IVI) was observed for Dalbergia sissoo Roxb. (IVI 20.54). The biodiversity index for other vegetation structures is 3.234, 2.976, and 1.242 for herbs/shrubs, grasses, and climbers respectively.